ANALYSIS OF CHANGES IN THE MEANING OF WORDS IN THE CANON OF ISLAMIC SHARI’A IN PIDIE DISTRICT - Nuraiza, Nuraiza; Emilda, Emilda (International Journal of Social Science, 2023)
This study aims to determine changes in the meaning of words in the canon of Islamic law in Pidie Regency. The problem raised in this study is how changes in the meaning of words contained in the Canon of Islamic Shari'a in terms of the type of change and the factors that cause changes in meaning. The method used in this study is a qualitative descriptive method with a content analysis approach. The source of the data in this study was the texts of Kanun Syariat Islam in Pidie district which were compiled in the Aceh Islamic Law. The data from this study are words that experience changes in meaning in the text of Kanun Syariat Islam. Data collection is done by reading and note technique. Data analysis was carried out using qualitative analysis techniques with data selection procedures, data classification and data interpretation. The results of the study show that there are 9 forms of changes in meaning in Kanun Syariat Islam in Pidie district, namely expansion (generalization), narrowing (specialization), exaltation (amelioration), reduction (pejoration), exchange (synesthesia), equation (association), metaphor ( figurative meaning), euphemism (euphemism), and coarseness (dysphemia). The causes of the change in meaning found are historical factors, social factors, psychological factors, factors for the need for new words, and factors for exchange of responses